KORELASI FAKTOR PEMBENTUK PERSEPSI DENGAN PERSEPSI KONSUMEN TERHADAP MEDIA PEMASARAN ONLINE (www.goodplant.co.id) - Dita Wahyu Ningtyas Tuty; Emi Widiyanti; Bekti Wahyu Utami (Universitas Sebelas Maret, 2017)
The development of information technology has opened a business network, especially the Internet. Agribusiness actors have also started using the internet to market their products using the website. www.goodplant.co.id is an e-commerce that sells hydroponics products. This study is intended to identify the characteristic of perception maker of the consumers of goodplant.co.id, correlation of consumers’ perception maker characteristics and consumers’ perception of quality of goodplant.co.id as an online marketing media. This study applied a descriptive study through the survey. The subject of this study was people who have accessed the website, or people who have done any transaction on the website. The subject was chosen using judgment sampling by Google Docs. The amount of the subject is decided to use the estimation of population proportion and confidence level, which was made with 95% of 100 respondents. This study was conducted using two kinds of data, primary data, and secondary data. The data were analyzed using Kendall correlation. The result of the study showed that: (1) the age range of the respondents is 17 – 34 years old, (2) the education of the respondents are diploma/ undergraduate degree, (3) most of the respondents are an employee or entrepreneur, and having high revenue, (4) most of the also frequently do online shopping. There was a significant correlation between education, revenue, occupation, and online shopping experience toward the consumers’ perceptions of goodplants.co.id as an online marketing media. However, there was no significant correlation between the age range of the consumers with their perceptions of goodplants.co.id as an online marketing media.